A Comparison of China's "Ivy League" to Other Peer Groupings Through Global University Rankings. (November 2017) - Allen, Ryan M.
This article analyzes the People's Republic of China's elite-making higher education policies that began in the early 1990s, notably with the 211 Project and then 985 Project, which led to the formation of the C9 League, a group of nine leading institution's dubbed China's "Ivy League." This elite grouping is compared with other Chinese universities in terms of global rankings from 2003 to 2015 to ascertain the separation by these top tiered institutions. Furthermore, the C9 League will be compared with other global elite coalitions in the United States, Canada, Australia, and the United Kingdom over the same period. University rankings, despite considerable criticism, have provided the Chinese leadership with key benchmarks for their vision of world-class higher education. This article finds that the C9 League has made some separation from other Chinese universities and has also caught up with its Western peers (notably passing Canada's U15) in terms of international rankings.